Comparative Study of Educational Playing Cards and Animated Videos on Adolescent Girls' Knowledge and Awareness of Anemia - Agustin Widyowati; Riza Yuliawati; Ardi Bastian; Kristin Ernawati; Dian Mustikawati (Sean Institute, 2026)
Background. Adolescent girls are prone to anemia caused by puberty. The impact of anemia can be short-term or long-term which will indirectly affect economic and social development. Purpose. This study aims to analyze the effectiveness of educational game cards and the combination of educational game cards and animated videos on the knowledge and awareness of adolescent girls about anemia. Method. The design of this study uses pretest-posttest experimental control group design carried out in schools, under the auspices of the Baron Health Center which has received counseling from the health center. Participants in the blood supplement tablet (TTD) program were 201 young women with a simple random sampling technique. The control group received the treatment of educational game cards and the treatment group received a combination of educational game cards and animated videos. Result. The results of the Wilcoxon Test showed that there was a significant difference in the knowledge (0.000) and awareness (0.000) of adolescent girls about anemia before and after the intervention. The results of the Mann Whitney test showed that there was no significant difference between respondents who used educational game cards and a combination of educational game cards and animated videos on the knowledge (p-value: 0.686) and awareness (p-value: 0.171) of adolescent girls about anemia. Conclusion. The need to develop appropriate and fun educational media for young women to increase their knowledge and awareness in the treatment and prevention of anemia.